A STUDY TO EVALUATE USERS’ SATISFACTION OF BLACKBOARD LEARN - Hossain, Md Mokter; Akhtar, Shakil; Rahman, Muhammad Asadur (PEOPLE: International Journal of Social Sciences, 2017)
This study summarizes and reports first-time users’ satisfaction of a Blackboard Learn user interface that had been adopted as an online/blended teaching-learning management tool. Users’ satisfaction was measured in terms of the overall consistency, ease of use, universability, positive aspects, and problems/limitations of the Blackboard Learn user interface. Data were collected through a number of 5-point Likert scale type items using an online survey. The survey also gathered participants’ gender and major area of study to determine if there exists any significant difference in their satisfaction, among the possible groups in these measures. Results revealed that first-time Blackboard Learn users are most likely overall satisfied in using it without any significant difference among male vs. female; and engineering vs. non-engineering major users. Blackboard users are satisfied with a number of its advanced features, although they have reported some noticeable problems, limitations, and recommendations.